2017
DOI: 10.1002/jum.14347
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficiency of Quantitative Contrast‐Enhanced Ultrasound Indicators for Discriminating Benign From Malignant Solid Thyroid Nodules

Abstract: Quantitative contrast-enhanced US indicators help discriminate benign from malignant thyroid nodules. The nodule-to-perinodule peak intensity ratio showed the best diagnostic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
2
27
0
5
Order By: Relevance
“…The main reason that thyroid malignant tumors show a lack of blood supply is that the tumors grows with complex neovascularization inside it; once the growth outweighs neovascularization, necrosis and embolus formation happens within the tumor, ultimately leading to hypoenhancement on CEUS. Moreover, Zhou et al [ 20 ] found that instead of hypoenhancement, the nodule-to-perinodule peak intensity ratio showed the best diagnostic efficiency, with an optimal cutoff value of 0.9.…”
Section: Ceus Patterns Characteristic Of Malignant Thyroid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason that thyroid malignant tumors show a lack of blood supply is that the tumors grows with complex neovascularization inside it; once the growth outweighs neovascularization, necrosis and embolus formation happens within the tumor, ultimately leading to hypoenhancement on CEUS. Moreover, Zhou et al [ 20 ] found that instead of hypoenhancement, the nodule-to-perinodule peak intensity ratio showed the best diagnostic efficiency, with an optimal cutoff value of 0.9.…”
Section: Ceus Patterns Characteristic Of Malignant Thyroid Nodulesmentioning
confidence: 99%
“…A previous study [ 41 ] reported that the combination of US, RTE, and CEUS could increase both the sensitivity and specificity of all three methods. With regard to comparisons between individual methods, most studies [ 20 , 42 , 43 ] showed that RTE was the most valuable tool. Giusti et al [ 44 ] found that RTE and CEUS showed no advantages over US, and in a further study, demonstrated that the information added by CEUS was less sensitive than that provided by US and RTE.…”
Section: Ceus Combined With Real-time Elastography and Conventional Umentioning
confidence: 99%
“…Is an FNA biopsy indicated in cases involving combined calcification in the same nodule, even if a high risk of a false negative has been described? In a retrospective study, Zhou et al [12] studied the quantitative contrast-enhanced US indicators for discriminating between benign and malignant thyroid nodules. The authors concluded that quantitative contrast-enhanced US may be useful and that the nodule to peri-nodule peak intensity ratio showed the best diagnostic efficacy; however, the situation remains unclear and controverted.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, researchers have demonstrated that, under CEUS, ring enhancement showed an accuracy of 88.5% for benign lesions, and heterogeneous enhancement showed an accuracy of 90.4% for malignant lesions (22). Li et al (23) concluded that low, weak, or uneven enhancements are valuable perfusion features for evaluating papillary thyroid carcinoma but that a uniform, high-enhanced perfusion mode was typical of benign nodules.…”
Section: Discussionmentioning
confidence: 99%